Changes in day–night dominance of combined day and night heatwave events in China during 1979–2018 - Shengjun Gao; Yunhao Chen; Kangning Li; Bin He; Ying Cui; Peng Hou (Environmental Research Letters, 2022)
China has experienced varying degrees of increase or decrease in daytime and nighttime heatwaves, but studies have mostly been at the site or grid scale, and it remains unclear how daytime and nighttime heatwave events in China vary regionally when spatial scales are considered. Here, we redefine the different types of heatwave events in China from 1979 to 2018 as combined day and night heatwave events (CDNHWEs) and independent daytime (nighttime) heatwave events. Due to more pronounced spatiotemporal characteristics, CDNHWEs are the dominant heatwave events in China. Further analysis of the dominant heatwave events indicates that their increase in intensity is stronger at night than during the day, i.e. for CDNHWEs, the daytime-dominated events are gradually replaced by nighttime-dominated events. Compared to 1979–2003, there has been an increase in dominant heatwave events mainly in the south during the day and a nationwide increase at night since 2004. For CDNHWEs, daytime and nighttime processes are regulated by different mechanisms. During the daytime, fewer clouds enhance solar shortwave radiation, favouring daytime heatwaves; however, the increase in aerosols in northern China suppresses solar shortwave radiation. At night, the increase in humidity allows for increased longwave radiation, which favours the formation of nighttime heatwaves across the country. These findings further demonstrate the regional variability of heatwave hazards experienced in China and that targeted heatwave-mitigation measures should be developed based on regional characteristics.